Aircraft mathematical model with account of vortex sheet dynamics - Пахненко, В. В. (Proceedings of National Aviation University (archive), 2000)
Constructed is mathematical model of aircraft in the roll channel regime of air inertia rotation with the account of vortex sheet dynamic, including common differential equations characterizing the aircraft dynamic motion, and the state of vortex sheet aerodynamic characteristics depends on running variables of vortex sheet state